Relations between ethnographic museums and African and Oceanic art markets in France, Switzerland and Belgium : building value(s) and appropriating otherness - (:unkn) unknown (My University, 2018)
This PhD thesis presents the valuation of ethnographic object through the prism of their circulation between two stakeholders : art markets and ethnographic museums. No scientific research has so far looked in depth at the relation between this two actors in the tribal art’s field, except to describe or criticise the specific case of the Musée du quai Branly-Jacques Chirac’s foundation.My research mobilising anthropology and museology is based on intensive fieldwork with galleries, auction houses and museums in Switzerland, France and Belgium between 2013 and 2017. The comprehensive analysis shows the territorial issues between this different stakeholders and highlights the increase in events both in museums and markets. My research also draws a portrait of the market, its functionning and its hierarchies and proposes a typology of the different relations and actors. The main objective was to understand the process of fixing an object’s value. In a market dominated by speculation and a lot of arbitrariness, I highlight that this value is intrinsically linked to the control of information. Finally, the analysis shows the « how-to-think » and processes developped by all the actors in the field to rationalise some of these speculative practices. I hope I have emphasised in this work the new forms of production, appropriation, consumption and the valorisation of otherness by our society today.
Keywords: African Research